2006
DOI: 10.1111/j.1439-0450.2006.00950.x
|View full text |Cite
|
Sign up to set email alerts
|

Prevalence and Pathogenicity of Cryptosporidium suis in Pre‐ and Post‐weaned Pigs

Abstract: A total of 4338 faecal samples, 135 of sows, 3368 of pre-weaned and 835 of post-weaned piglets from eight farms in South Bohemia, Czech Republic were collected and examined for Cryptosporidium infection. No sow, but 5.7% pre-weaned and 24.1% post-weaned piglets were positive for Cryptosporidium infection. No relationship was found between diarrhoea and Cryptosporidium infection in any of the different age groups (pre- and post-weaned piglets). Four piglets, which were sporadically shedding cryptosporidia in fa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

7
26
2

Year Published

2010
2010
2022
2022

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 48 publications
(35 citation statements)
references
References 26 publications
7
26
2
Order By: Relevance
“…Our observation that the nursery operation, which has two houses and a 0.3-ha lagoon, compared to the finishing operations with four houses and 0.6-ha lagoons, had the greatest concentration of oocysts is in agreement with the observation of Vitovec et al (34). They reported that the greatest prevalence of Cryptosporidium oocysts in porcine fecal samples was associated with postweaning piglets between 6 and 8 weeks old.…”
Section: Discussionsupporting
confidence: 82%
“…Our observation that the nursery operation, which has two houses and a 0.3-ha lagoon, compared to the finishing operations with four houses and 0.6-ha lagoons, had the greatest concentration of oocysts is in agreement with the observation of Vitovec et al (34). They reported that the greatest prevalence of Cryptosporidium oocysts in porcine fecal samples was associated with postweaning piglets between 6 and 8 weeks old.…”
Section: Discussionsupporting
confidence: 82%
“…Cryptosporidium oocysts are resistant to standard chlorination, may prevail in water environments, and some species have the ability to infect various animals species. Cryptosporidia are recognized as important parasitic protozoa causing asymptomatic to severe intestinal infections of animals and humans, depending on various factors including the immunological capabilities of their host (Vítovec et al 2006;Hamnes et al 2007;Langkjaer et al 2007;Zintl et al 2007;Armson et al 2009;Ryan and Xiao 2009;Chen et al 2011;Budu-Amoako et al 2012). …”
Section: Introductionmentioning
confidence: 99%
“…Cryptosporidium suis (previously known as pig genotype I) and Cryptosporidium scrofarum (previously known as pig genotype II) are commonly detected in pigs, and have been shown to be host specific (Morgan et al 1998;Enemark et al 2003;Guselle et al 2003;Ryan et al 2003Ryan et al , 2004Xiao et al 2006;Hamnes et al 2007;Langkjaer et al 2007;Suárez-Luengas et al 2007;Johnson et al 2008;McCarthy et al 2008;Vítovec et al 2006;Kváč et al 2013). Natural porcine cryptosporidiosis has then been reported worldwide with the infection rates ranging between 0 and 87.5 % (Quílez et al 1996;Chen and Huang 2007;Hamnes et al 2007;Langkjaer et al 2007;Suárez-Luengas et al 2007;Yatswako et al 2007;Zintl et al 2007;Johnson et al 2008;Armson et al 2009;Kváč et al 2009a, c;Ryan and Xiao 2009;Budu-Amoako et al 2012;Chen et al 2011;Jeníková et al 2011;Nguyen et al 2012a).…”
Section: Introductionmentioning
confidence: 99%
“…Pigs are natural hosts for both C. suis and C. scrofarum (previously known as Cryptosporidium pig genotype II) (Vítovec et al 2006, Hamnes et al 2007). The infections caused by these parasites were reported in pigs in Europe with a herd prevalence from 1.4% to 62.5% depending on the age of the tested animals (Wieler et al 2001, Mišić et al 2003).…”
Section: Discussionmentioning
confidence: 99%